Carbonate associated uranium isotopes as a novel local redox indicator in oxidatively disturbed reducing sediments. (15th October 2021) - Clarkson, Matthew O.; Hennekam, Rick; Sweere, Tim C.; Andersen, Morten B.; Reichart, Gert-Jan; Vance, Derek
Abstract: The interpretation of local redox indicators in marine sediments relies on their preservation. By their nature, such biogeochemical tracers are susceptible to diagenetic alteration, particularly through post-depositional re-oxidation of the sediment. This can result in the mobilization and loss of distinctive redox dependant signatures, leading to the classical problem that the presence of oxygenated conditions cannot be robustly inferred by the absence of evidence for anoxia. Authigenic uranium enrichments, and their isotope signatures (δ 238 U), are widely used to infer bottom-water and pore-water redox conditions but are susceptible to later oxidative diagenetic disturbance. Here we explore the preservation of authigenic δ 238 U signatures in sediment samples from Sapropel S1 at Site 64PE406-E1 in the Eastern Mediterranean Sea (~1760 m water depth), which was originally deposited under reducing conditions but severely affected by later oxidative diagenesis and the variable loss of authigenic U(IV) from the upper sapropel. To this end, we compare U isotope signatures from bulk measurements (δ 238 Ubulk ) with detrital corrected authigenic U (δ 238 Uauth ) and carbonate associated U (δ 238 UCAU ). In contrast to open ocean carbonates deposited under fully oxic conditions, sapropelic carbonate leachates yield δ 238 UCAU similar to calculated δ 238 Uauth, thus recording (predominantly) redox dependant isotope fractionation. There is no evidence for significant isotope fractionation resulting from post-depositional oxidative diagenesis, but associated authigenic U(IV) removal results in larger relative detrital contributions to δ 238 Ubulk, and hence large uncertainties on δ 238 Uauth estimates. By contrast, δ 238 UCAU successfully avoids detrital phases, and the uncertainty associated with detrital corrections, providing a primary record of changes in local redox conditions. Thus, we propose that δ 238 UCAU can be used for accurate reconstructions of benthic de-oxygenation in sediments with low U enrichments, including sediments with post-depositional U(IV) loss and less reducing environments.